Developing computer-assisted learning tool based on discovery learning to improve students' mathematical reasoning - Siregar, Ginda Maruli Andi; Wahyudin; Herman, Tatang; Prabawanto, Sufyani (Universitas Islam Negeri (UIN) Mataram, 2023)
[English]: Mathematical reasoning abilities were needed in solving steps using mathematics numerically. In mathematics education, students always had difficulty building solution steps into algorithms and were unable to build program code. The cause of these difficulties and failures was learning obstacles in the form of didactical obstacles. Learning did not facilitate the development of mathematical reasoning abilities for building algorithms and program code. It was not only the use of inappropriate teaching methods but also the limitations of teaching tools, such as computers, in creating a program. Mathematics and informatics students encountered this issue during their learning journey in numerical methods courses, experiencing both low mathematical reasoning abilities and restricted access to computer lab facilities within their department. The research carried out was to develop and evaluate computer-assisted learning based on discovery learning. The method in this research used a quantitative approach to obtain a quantitative evaluation of the development of computer-assisted learning using the web, which was developed through research and development in the ADDIE model. The web was used as a computer-assisted learning tool in the very valid category by media experts, mathematicians, and test respondents. The results of pre- and post-tests of mathematical reasoning ability were analyzed using a paired t-test, obtaining a significant value of 0.609 above the significance level of 0.05, indicating that computer-assisted learning through web-based discovery learning could be used to enhance students' mathematical reasoning abilities. Direct observations also showed increased engagement and facilitated improvement in students' mathematical reasoning abilities. A weakness to note was the relatively longer time usage, as instructors received many responses from students and provided repeated guidance to align with the steps of discovery learning within the web media. [Bahasa]: Kemampuan penalaran matematika dibutuhkan dalam langkah-langkah penyelesaian dengan matematika secara numerik. Mahasiswa pendidikan matematika selalu kesulitan dalam membangun langkah penyelesaian menjadi algoritma, dan tidak mampu membangun kode program. Penyebab kesulitan dan kegagalan tersebut adalah hambatan belajar berupa didactical obstacle. Pembelajaran tidak memfasilitasi pengembangan kemampuan penalaran matematis dalam membangun algoritma dan kode program. Bukan hanya penggunaan metode ajar yang tidak sesuai, tetapi juga keterbatasan alat-alat ajar, seperti komputer dalam pembuatan sebuah program. Masalah ini dihadapi oleh mahasiswa matematika dan informatika dalam proses belajar pada matakuliah metode numerik, yaitu rendahnya kemampuan penalaran matematis serta keterbatasan penggunaan fasilitas lab komputer di jurusannya. Penelitian yang dilakukan adalah membangun dan mengevalusi pembelajaran berbantuan komputer yang berbasis discovery learning. Metode dalam penelitian ini menggunakan pendekatan kuantitatif dalam memperoleh evaluasi secara kuantitas dari pengembangan pembelajaran berbantuan komputer menggunakan web yang dikembangkan melalui research and development dengan model ADDIE. Web yang digunakan sebagai alat pembelajaran berbantuan komputer dikategorikan sangat valid oleh ahli media, ahli matematika, dan uji responden. Hasil pre-tes dan post-tes kemampuan penalaran matematis dianalsis dengan uji paired t-test memperoleh nilai signifikan sebesar 0.609 diatas level signifikansi 0.05 yang menunjukkan bahwa pembelajaran berbantuan komputer melalui web berbasis discovery learning dapat digunakan untuk meningkatkan kemampuan penalaran matematis mahasiswa. Observasi langsung juga memperlihatkan peningkatan keterlibatan dan memfasilitasi peningkatan kemampuan penalaran matematis mahasiswa. Kelemahan yang harus diperhatikan adalah penggunaan waktu yang relatif lebih lama karena pengajar memperoleh banyak tanggapan dari mahasiswa serta memberikan arahan berulang kali sehingga sesuai dengan langkah discovery learning di dalam media web.